Vivienda en una casa del siglo XIV, Barcelona - Martínez Lapeña-Torres (2002)
Rehabilitación de una vivienda en el barrio gótico en Barcelona
Keywords: MARTINEZ LAPEÑA, JOSE ANTONIO; TORRES, ELIAS; BARCELONA; ESPAÑA; REHABILITACION; VIVIENDAS UNIFAMILIARES